Outcome of Using Intraventricular Plus Intravenous Polymyxin B in Post-neurosurgical Patients With Multi/Extensively Drug-Resistant Gram-Negative Bacteria-Induced Intracranial Infection - Li, Hangyang; Yu, Wenqiao; Wang, Guobin; Cai, Hongliu (Frontiers in Medicine, 2022)
Introduction: Post-neurosurgical central nervous system (CNS) infection caused by multidrug-resistant (MDR)/extensively drug-resistant (XDR) Gram-negative bacteria remains a major clinical challenge. This study describes our experience of treating such patients with combined intraventricular (IVT) and intravenous (IV) polymyxin B administration. Methods: This retrospective study included six patients with post-neurosurgical CNS infections of carbapenem-resistant Acinetobacter baumannii (CRAB) or carbapenem-resistant Klebsiella pneumoniae (CRKP). All patients were treated in the intensive care unit (ICU) of First Affiliated Hospital, Zhejiang University School of Medicine (Hangzhou, China) between November 2020 and November 2021, and all received IVT plus IV polymyxin B. Data including patients’ characteristics, therapeutic process, symptoms, cerebrospinal fluid (CSF) examination, laboratory tests, and complications were collected. Results: Six patients with post-neurosurgical CNS infection were enrolled in the study. The patients comprised five males and one female, and the average age was 58 years (range, 38–73 years). Four out of the six cases were CRAB-positive in CSF culture, while two cases were CRKP-positive. The mean duration of polymyxin B administration was 14±5.69 days (range, 6–20 days). The average period of patients reaching CSF sterilization was 10.33±3.67 days (range, 5–14 days). All six cases were cured without acute kidney injury or epilepsy. Conclusion: IVT plus IV polymyxin B is a safe and effective treatment for post-neurosurgical patients with intracranial infection caused by MDR/XDR Gram-negative bacteria.